Perlindungan Hukum Atas Kriminalisasi Terhadap Notaris Karena Terjadinya Pembatalan Perjanjian Jual Beli Hak Atas Tanah - Pramana, I Gusti Ngurah Bagus; Swardhana, Gde Made (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 5 No 3 (2020), 2020)
This research is motivated by the existence of conflict norms in Article 16 paragraph (1) letter a UUJN with Article 16 paragraph (1) letter e UUJN. The notary is obliged to behave honestly in checking certificates at the land office, and to be careful in carrying out the sale and purchase agreement process, so as not to cause losses and problems in the future. At this writing, there are two problem formulations: what is the basis for the Notary for canceling the sale and purchase agreement of land rights and what is the legal protection for the criminalization of the Notary by the seller due to the cancellation of the sale and purchase agreement for land rights. The research objective is to find out the basis for the notary to cancel the sale and purchase agreement of land rights and to protect the notary from criminalization by the seller from the cancellation of the sale and purchase agreement of land rights. The legal research method uses normative legal research with a statutory approach and a conceptual approach. The results of the study show that the basis for the notary to cancel the sale and purchase agreement process is to act honestly, thoroughly, independently, and to protect the interests of the parties involved in legal actions and legal protection for criminalization of notaries by the seller because the cancellation of the sale and purchase agreement is a notary. can exercise his denial.